2013
DOI: 10.1016/j.jtcvs.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem and ex vivo carbon monoxide ventilation reduces injury in rat lungs transplanted from non–heart-beating donors

Abstract: Objective: We sought to determine whether ventilation of lungs after death in non-heart-beating donors with carbon monoxide during warm ischemia and ex vivo lung perfusion and after transplant would reduce ischemia-reperfusion injury and improve lung function. Methods: One hour after death, Sprague-Dawley rats were ventilated for another hour with 60% oxygen (control group) or 500 ppm carbon monoxide in 60% oxygen (CO-vent group; n¼6/group). Then, lungs were flushed with 20 mL cold Perfadex, stored cold for 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…A series of therapeutic strategies have been studied using EVLP for lung repair. For example, different drugs were delivered through perfusate to mitigate IRI [113][114][115] , therapeutic gases (NO, CO, H 2 ) were inhaled during EVLP to reduce inflammatory response and lung edema [116][117][118] , mesenchymal stem cells were used to treat lung injury induced by endotoxins and infection [119] , and IL-10 gene therapy was developed to prevent IRI [120,121] . When the types of injury are clear, injury-specific treatments can be used during EVLP.…”
Section: Organ Repairmentioning
confidence: 99%
“…A series of therapeutic strategies have been studied using EVLP for lung repair. For example, different drugs were delivered through perfusate to mitigate IRI [113][114][115] , therapeutic gases (NO, CO, H 2 ) were inhaled during EVLP to reduce inflammatory response and lung edema [116][117][118] , mesenchymal stem cells were used to treat lung injury induced by endotoxins and infection [119] , and IL-10 gene therapy was developed to prevent IRI [120,121] . When the types of injury are clear, injury-specific treatments can be used during EVLP.…”
Section: Organ Repairmentioning
confidence: 99%
“…Firstly, the refinement of donor selection was illustrated by the study of Sanchez et al, which showed that, despite similar clinical characteristics and alveolocapillary barrier properties after the period of cardiac arrest and warm ischemia, donor lungs that did not receive prearrest heparinization had significantly worse physiological performance on EVLP compared to lungs from donors that received pre-arrest heparin (32). Secondly, the normothermic and metabolically active environment restored by EVLP provides an ideal platform for therapeutic manipulation of the DCDD organ (33)(34)(35)(36). EVLP-treated lungs showed better posttransplant lung function and less microthrombi formation compared to no-EVLP lungs in a DCDD experimental study (37).…”
Section: Dcdd-no Evlp Vs Dcdd þ Evlpmentioning
confidence: 99%
“…EVLP has been utilized as an effective strategy for the assessment of marginal, high-risk donor lungs and has also demonstrated potential for expansion of the limited donor organ pool through the rehabilitation of DCD lungs (11-14). While current advancements in EVLP-mediated rehabilitation merit optimism concerning the future utilization of DCD lungs, two principle benefits to this approach that have not been adequately explored are the delivery of therapeutic, anti-inflammatory agents to the injured lung and the identification of molecular markers that may serve as predictors of PGD after transplantation.…”
Section: Introductionmentioning
confidence: 99%